2015
DOI: 10.1128/jvi.02007-14
|View full text |Cite
|
Sign up to set email alerts
|

A Human Herpesvirus 6A-Encoded MicroRNA: Role in Viral Lytic Replication

Abstract: Human herpesvirus 6A (HHV-6A), a member of the betaherpesvirus family, is associated with several human diseases. Like all herpesviruses, HHV-6A establishes a lifelong, latent infection in its host. Reactivation of HHV-6A is frequent within the immunosuppressed and immunocompromised populations and results in lytic viral replication within multiple organs, often leading to severe disease. MicroRNAs (miRNAs) are key regulators of multiple cellular processes that regulate the translation of specific transcripts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 43 publications
3
53
0
Order By: Relevance
“…For instance, HCMV-encoded miR-UL112-1 regulates a variety of genes by binding to the 3= untranslated region (UTR) of viral transcripts and inhibiting translation (9). Human herpesvirus 6A (HHV-6A)-encoded miR-U86 targets the HHV-6A U86 immediate-early (IE) gene, thereby regulating lytic replication (35). These findings suggested that a virus-encoded miRNA modulates its own replication process and infection status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, HCMV-encoded miR-UL112-1 regulates a variety of genes by binding to the 3= untranslated region (UTR) of viral transcripts and inhibiting translation (9). Human herpesvirus 6A (HHV-6A)-encoded miR-U86 targets the HHV-6A U86 immediate-early (IE) gene, thereby regulating lytic replication (35). These findings suggested that a virus-encoded miRNA modulates its own replication process and infection status.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous computational analysis predicted an HBV miRNA (34), we did not get the predicted miRNA sequence. Generally, the tools for identifying novel miRNAs were Northern blotting and stem-loop RT-qPCR (7,(35)(36)(37)(38) and bioinformatics analysis for predicating the secondary structure of candidate miR precursors. Bioinformatics analysis predicted the precursor structure and found that one hairpin structure contained HBV sncRNA-3 and -5 at two stems, which were named HBV-miR-3-3p and HBV-miR-3, and they are conserved in various HBV strains.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free virus stocks were generated by concentrating the supernatant of highly infected JJHan cells and titrated by analysing the genome copies in newly infected cells by qPCR. Multi-step growth kinetics (Oyaizu et al, 2012;Nukui et al, 2015) revealed that the DU94 mutant had a significant growth defect compared to the wt and revertant virus (Fig. 1c), suggesting that the impaired HHV-6A replication is either due to the abrogation of U94 expression or effects on neighbouring genes such as U95 caused by deletion of the U94 sequences.…”
mentioning
confidence: 99%
“…1b) as described previously (Kaufer et al, 2011). The recombinant viruses were subsequently reconstituted by nucleofection of JJHan cells with the HHV-6A BAC DNA as described previously (Nukui et al, 2015). Cell-free virus stocks were generated by concentrating the supernatant of highly infected JJHan cells and titrated by analysing the genome copies in newly infected cells by qPCR.…”
mentioning
confidence: 99%
“…Although viral miRNAs evolved independently in the three herpesvirus subfamilies, repression of viral immediate early (IE) genes is a common theme [17,36,37,[48][49][50]. Repression is best exemplified by herpes simplex virus 1 and 2 (HSV-1 and HSV-2), where viral miRNAs derived from the latency-associated-transcript (LAT) are expressed antisense to key IE genes, thereby allowing for strong suppression of ICP0, ICP4 and ICP34.5 [17,51].…”
Section: Micrornas In Latency and Reactivationmentioning
confidence: 98%